Vivência de violência na infância e adolescência: impacto na personalidade e reconhecimento de emoções - Ferro, Luiz Roberto Marquezi (2021)
Studies that address maltreatment in childhood and adolescence have become relevant over the last few years given the evidence of harmful repercussions in the psychological sphere of their victims. The aim of this study was to evaluate cognitive, personality and emotional recognition aspects of children and adolescents exposed to situations of violence. Method. The research consisted of two phases. To calibrate the chosen instruments, we carried out a pilot phase, the data from this phase were included in the general survey. Phase 1 was carried out through a survey survey, consisting of 100 participants, divided into two groups. A group of children who were cared for in a vulnerable care institution (children participating in the Center), with the possibility of evidence of Domestic Violence (50 participants) and another group of children of the same age who studied at a private school (children enrolled at the College) (50 participants). The sample of children was evaluated with the following instruments: Domestic Violence Phrases Inventory (IFVD), the Wechsler Short-Branch Intelligence Scale (WASI), the Personality Questionnaire for Children and Adolescents (EPQ-J), the Parental Style Inventory (IEP) to assess parental relationships and the Computerized Neuropsychological Battery (PennCNP) along with the University of Pennsylvania Emotion Recognition Test (ER40). We obtained as results two groups with evidence of VD and those without evidence of VD x Colégio and Nucleus. In the WASI test, using the ANCOVA statistical test with the variables age, gender, school year, we found significance in the College group (p<0.01), evidencing better Total IQ score. Regarding Personality, through ordinal multinominal logistic regression we found significance in the Psychoticism and Neuroticism domains (p<0.01) for members of the Nucleus; and for the Sincerity domain for the members of the Nucleus (0.02) and the group without DV (p<0.01). For parenting style, the Fischer test showed better scores for the College group (p<0.01), unlike the VD group (p<0.01). In the analysis of facial emotions, the ANCOVA statistical test and the binomial logistic regression model presented significance p<0.01 for the College group. Regarding the EDF40 test, there was significance in the success of the Happy Response (p<0.01 College group and 0.02 without VD), Sad Right Response (p<0.01 College group) and Total Correct Response (p<0, 01 College group). In ER40 there was significance Correct Identification of Anger, Correct Identification of Fear and Correct Identification of Happy, Correct Identification of Sad (p<0.01 for the College group). For the Correct Neutral Identification there was significance for the College group and without VD (0.01). Phase 2 had the group of parents and/or guardians from phase 1, and they were also categorized into 2 groups (College-College x with VD and without VD). The instruments used were a sociodemographic questionnaire, the WASI scale for assessing intelligence, the NEO FFI-R instrument to assess personality, and a scale for assessing peer violence CTS-2. The ANCOVA statistical test used to measure the statistical significance in intelligence showed significance for the College group in the domains Verbal IQ, Execution IQ and Total IQ (p<0.01). Regarding violence between peers, Poison regression was significant for almost all domains of violence for the Nucleus group (p<0.01), with the exception of Severe Sexual Coercion, which was significant for the group with evidence of HV (p <0.01). Regarding personality, the multinomial ordinal logistic regression model presented significance in the Neuroticism domains (p<0.01) for the Nucleus group, for the Extroversion domain there was significance for the College group (p<0.01), for the Openness domain there was significance for the College group (p<0.01) and without HV (0.03), in the Ability domain there was significance for the College group (p<0.01) and without HV (0.02) and the Conscientiousness domain for the Colégio group and without DV (0.03 both). Comparing the variable intelligence of parents and children with VD using the Spearman test, there was a weak significance in Verbal IQ. Comparing personality by the McNemar test, there was a difference between Neuroticism of children and parents, with parents presenting higher classifications than children. Thus, children who have the opportunity to grow up with quality education, with emotionally balanced families, tend to have a lower incidence of violent behavior, cognitive impairment and personality disorders.(AU)